Limited effects of parsley (Petroselinum crispum) on protein glycation and glutathione in lenses of streptozotocin-induced diabetic rats - AKBAY, TUĞBA (SWETS ZEITLINGER PUBLISHERS, 2001)
Parsley (Petroselinum crispum), which has hypoglycaemic activity, has been used as a folk remedy for diabetes. This study investigated the effect of parsley administration on diabetes-induced impairments in rat lenses. Administration of parsley extract did not prevent a decrease in glutathione nor an increase in protein glycation, although it did significantly prevent an increase in blood glucose. SDS-polyacrylamide gel electrophoresis revealed no significant differences in any protein bands between any of the groups.
Keywords: lens; diabetes; parsley; glutathione; protein; glycation; electrophoresis; SKIN